FUNDAMENTAL ASPECTS OF A THIRD COMPONENT USED IN TERNARY SOLID DISPERSION: A REVIEW - S., SREE VARSHINI; C., VAIYANA RAJESH (International Journal of Applied Pharmaceutics, 2021)
Ternary solid dispersion (TSD) is one of the promising approaches used in recent studies to address the issues encountered by poorly water-soluble drugs. The binary solid dispersion (BSD) with the drug and the single polymer is not sufficient to satisfy all the criteria such as improved solubility, dissolution, stability, supersaturation, and recrystallization inhibition. Hence, the TSD with the third component/ternary agent aids in overcoming the limitations, thereby enhancing the solubility and bioavailability to a greater extent when compared to the BSD. Excipients that can be used as a third component includes surfactants, pH modulator, polymer and adsorbents. All these excipients have distinct benefits in improving the efficiency of the final dosage form. However, care must be taken in selecting suitable excipients for the research. This review highlights the impact of these excipients in improving the formulation complications and the therapeutic potential of the TSD.